Scientific collaborations and research trends in Parent-Child Interaction Therapy: a bibliometric analysis - Ulaş, Sümeyye; Seçer, İsmail; Victory, Erinn J.; McNeil, Cheryl B. (Frontiers in Psychology, 2023)
Parent-Child Interaction Therapy (PCIT) is considered to be an effective intervention for children aged 2-7 years with conduct problems. PCIT research has been conducted for approximately 50 years; however, an analysis of general research patterns has not been published. In this context, the present study outlines a bibliometric analysis of scientific collaborations, prevalence across locations on the basis of countries and organizations, leading researchers, and trends within PCIT research. Findings demonstrate that PCIT is an area in which international scientific collaborations are intense and current, and collaborations continue to be formed around the world. Additionally, results indicate that dissemination of intercultural PCIT adaptations are continuous.